2006
DOI: 10.1111/j.1365-2621.2006.tb12402.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre‐drying treatments on Quality and Safety of Sun‐dried Tomatoes. Part II. Effects of Storage on Nutritional and Sensory Quality of Sun‐dried Tomatoes Pretreated with Sulfur, Sodium Metbisulfite, or Salt

Abstract: Pre-drying treatments have been found to improve the quality of stored sun-dried tomatoes. Based on previous investigation (Part I), 5 specific pretreatments were chosen for effects on nutritional value, sensory quality, and safety before and after 3 mo of storage (25 °C and 30% to 34% relative humidity). These pretreatments included (1) direct gas sulfuring with 2.3 kg (5 lb) SO 2 ; (2) with 3.6 kg (8 lb) SO 2 ; (3) dipping in 10% salt for 5 min; (4) 8% sodium metabisulfite for 5 min; and (5) 8% sodium metabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The observed variations in DPPH and ß-carotene were 42.01 to 51.36 and 40.02 to 48%, respectively [21] The higher antioxidant activity of tea flavonoids is attributed to the presence of a specific chemical structure dominated by vicinal dihydroxy and trihydroxy moieties that can quench metal ions and imparted electron delocalization thus ultimately proved helpful to reduce free radicals production. [22,23] The more extraction efficiency of ethanol for polyphenol as compared to other solvents are in harmony with the findings of Friedman et al,; Ghasemzadeh et al,; Ghasemzadeh et al, [24][25][26] they observed better tea polyphenol extraction through aqueous ethanol as compared to methanol and water. In this context, they elucidated solvent-to-material ratio, time and temperature can play a vital role.…”
Section: ±6 Csupporting
confidence: 82%
“…The observed variations in DPPH and ß-carotene were 42.01 to 51.36 and 40.02 to 48%, respectively [21] The higher antioxidant activity of tea flavonoids is attributed to the presence of a specific chemical structure dominated by vicinal dihydroxy and trihydroxy moieties that can quench metal ions and imparted electron delocalization thus ultimately proved helpful to reduce free radicals production. [22,23] The more extraction efficiency of ethanol for polyphenol as compared to other solvents are in harmony with the findings of Friedman et al,; Ghasemzadeh et al,; Ghasemzadeh et al, [24][25][26] they observed better tea polyphenol extraction through aqueous ethanol as compared to methanol and water. In this context, they elucidated solvent-to-material ratio, time and temperature can play a vital role.…”
Section: ±6 Csupporting
confidence: 82%
“…This was the opinion of (43), who stated that increased brightness indicates inhibition of browning by sulfites. (44) added that using SMB can reduce color degradation and extend shelf life. Interestingly, in the preference test, there was an increase in the preference value with the addition of 6% SMB, followed by a decrease at a higher concentration.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The fresh tomato samples were sorted, graded, washed in water and then sliced into halves and quarters before pretreated. Tomato slices were immersed in 10% NaCl solution for 3 min according to latapi and Barrett (2006). Therefore, treatments were named as "non-pretreated-quarter, nonpretreated-half, pretreated-quarter and pretreatedhalf".…”
Section: Drying Proceduresmentioning
confidence: 99%
“…However, the natural convection solar dryers exhibit highly low buoyancy inside dryer (BAlA et al, 2003). Furthermore, conventional dryers are not economic because of high energy cost (gURlEk et al, 2009). At the other side, solar tunnel drier can be operated by a fan driven by photovoltaic module and this system removes moisture inside dryer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation